ANALYSIS OF THE FINANCIAL HEALTH OF BANK SYARIAH INDONESIA THROUGH LIQUIDITY RATIOS (CASH RATIO, FDR, AND LCR) FOR THE PERIOD 2021-2023 - Wahyu Dewi Hapsari; Budi Barata Kusuma Utami (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The article examines the financial health of Bank Syariah Indonesia (BSI) through liquidity ratios—Cash Ratio, Financing to Deposit Ratio (FDR), and Liquidity Coverage Ratio (LCR)—during 2021-2023, a period marked by post-pandemic recovery and economic uncertainties. Drawing on literature from Brigham & Houston (2021), IFSB (2021), and OJK (2023), the study employs a quantitative descriptive methodology, analyzing BSI's financial reports to assess liquidity performance. Results reveal a stable Cash Ratio (20%-50%) an optimal FDR (73%-81%), and a high LCR (above 100%), demonstrating BSI's effective liquidity management and adherence to sharia principles. The findings highlight BSI's strong financial health but emphasize the need for proactive liquidity management to navigate future economic challenges.